Strategi pembelajaran bahasa Arab yang efektif pada tingkat pelajar - Ain, Failla Aylana (Maliki Interdisciplinary Journal, 2024)
Learning Arabic is learning a outside dialect which is considered troublesome by most understudies, in truth Arabic is simple. Methodologies are required so that understudies don’t discover it troublesome. Arabic dialect learning methodologies are carried out so that understudies can get the fabric more succesfully. The choice of technique must be based on the dialect abilities instructed to understudies. A few methodologies that must be considered, specifically preparatory learning exercises, passing on data, understudy cooperation, tests, and follow up exercises. There are various types of Arabic language learning methods that can be used to achieve learning objectives.